Generalizacion en Cuba del programa de manejo integrado del acaro rojo tetranychus tumidus en platano - Almaguel, L.=700 1 Perez, P.; Ramos, M.
(Es, En)
Ilus., 21 ref.
Keywords: PLATANO; ACARO; GESTION DE LUCHA INTEGRADA; CUBA